Role of Rifaximin for the Treatment of Hepatic Encephalopathy in Chronic Liver Disease - Paul, Ranjit Kumar; Datta, Indrajit Kumar; Ahmed, Habib; Karim, Mohammad Reazul; Haque, Md Nazmul; Bhuiyan, Tareq M (BIRDEM Medical Journal, 2017)
Background: Hepatic encephalopathy (HE) is a common problem in patients with chronic liver disease (CLD) and is characterized by diminished mentation and neuromuscular abnormalities. Rifaximin has been reported to be effective for the treatment of hepatic encephalopathy (HE) in Europe and other countries. It is unknown whether rifaximin is effective for the treatment of hepatic encephalopathy in Bangladeshi patients. Methods: A prospective, randomized, single blind, placebo controlled study was conducted to evaluate the efficacy of rifaximin among patients with cirrhosis of liver with hepatic encephalopathy. A total sixty patients of HE fulfilling inclusion criteria were randomly enrolled among those admitted under Gastrointestinal, Hepatobiliary and Pancreatic Disorders (GHPD) department of BIRDEM General Hospital during August 2012 to April 2013. Patients were divided into two groups: group A (receiving Tab. rifaximin with lactulose), the total number of patients were 31(51.7%) and group B (receiving placebo with lactulose), it was 29(48.3%). Enrolled patients were followed up for 10 days or up to discharge from the hospital or death. At enrollment and at the end of treatment, gradation of HE and estimation of portosystemic encephalopathy (PSE) index was done. Results: In this study between two groups, mean age difference (p=0.404), gender difference (p=0.668) and CLD duration difference (p=0.555) were not statistically significant between two groups. At enrollment, prognostic scores e.g. Child-Turcotte-Pugh (CTP) score (p=0.489) and PSE index (p=0.934) were not significantly different between two groups. At the end of treatment, group A patients showed significantly lower HE grade (P=0.045) and PSE index (P<0.05) than group B. CTP score (p=0.552) was also lower in rifaximin treated group than placebo group but no significant difference was observed. The mean duration of hospital stay was significantly lower in group A than group B (p<0.05). Conclusions: Hepatic encephalopathy patients treated with rifaximin plus lactulose have better outcome and less hospital stay than those treated with placebo plus lactulose. Birdem Med J 2017; 7(3): 205-211